Multi-Hazard Vulnerability Assessment of an Urban Area: A Case Study on Ward 34 of Dhaka South City Corporation - Rahman, M Maksudur; Aktar, Shamima; Md Ashikuzzaman, - (Journal of the Asiatic Society of Bangladesh, Science, 2017)
Multi-hazard assessment provides the scope to understand the vulnerability situation of any area based on different hazard context. This study was conducted in one ward of Dhaka city corporation area to examine its multi-hazard vulnerability. Three key potential hazards: fire, earthquake and water-logging were considered to implement the multihazard analysis framework. To perform the analysis entire study area was surveyed and examined applying Geographic Information System in terms of practicing planning rules and regulation of Government of Bangladesh. All the structures of the study area were assessed and categorized into four classes ranging from severe to none according to some vulnerability criteria defined by safety standards. Individual vulnerability analysis was performed to realize the hazard specific vulnerability context. Finally, single processed hazard maps were combined to examine the multi hazard vulnerability of this study area. These findings denote that there are a certain number of structures in very risk position which should receive immediate hazard mitigation measures. Asiat. Soc. Bangladesh, Sci. 43(2): 181-195, December 2017